2014
DOI: 10.1111/fwb.12333
|View full text |Cite
|
Sign up to set email alerts
|

Niche differentiation among invasive crayfish and their impacts on ecosystem structure and functioning

Abstract: 2. Two fully-factorial mesocosm experiments (one for each crayfish pair) were used to investigate crayfish diet, and their impact on benthic invertebrate community structure, benthic algal standing stock and leaf litter decomposition rates, in allopatric and sympatric populations, compared to a crayfish free control. We used stable isotope analysis to examine crayfish diet in the mesocosms and in allopatric populations of each species in the Thames catchment.3. Isotopic niche width did not vary significantly b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
106
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(116 citation statements)
references
References 78 publications
8
106
2
Order By: Relevance
“…Sensitive native species are likely to be negatively affected by a single invasive animal species and therefore, when additional invasions occur they are often already locally extinct or significant reduced in abundance. For instance, if both invasive species have similar feeding strategies, the same native taxa are likely to be consumed by either invader, whether the invasion is single-or multi-species (Jackson et al 2014). Therefore, antagonistic interactions are of concern from a conservation perspective, since both invasive animals may need to be controlled to produce ecological recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Sensitive native species are likely to be negatively affected by a single invasive animal species and therefore, when additional invasions occur they are often already locally extinct or significant reduced in abundance. For instance, if both invasive species have similar feeding strategies, the same native taxa are likely to be consumed by either invader, whether the invasion is single-or multi-species (Jackson et al 2014). Therefore, antagonistic interactions are of concern from a conservation perspective, since both invasive animals may need to be controlled to produce ecological recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Both native and invasive crayfish can affect plant and animal communities through predation (e.g. Charlebois and Lamberti 1996;Axelsson et al 1997;Parkyn et al 1997;Nyström et al 2001;Dorn and Mittelbach 2004;Usio and Townsend 2004;McCarthy et al 2006;Jackson et al 2014;Moorhouse et al 2014), demonstrated by their consistently strong negative effects on plant biomass, other macroinvertebrates, fish and amphibian eggs and larvae. Additionally, crayfish are likely to directly compete with other organisms for resources (Bubb et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the influence of invasive taxa are often far reaching, with impacts ranging from the replacement of individual species to the modification of ecosystem processes (Riccardi, 2007;Jackson et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…As invasive crayfish extend their range, understanding their effects on biodiversity and ecosystem services is increasingly important for informing management strategies (Lodge et al, 2012;Jackson et al, 2014;Moorhouse et al, 2014). Despite the widely acknowledged threat that invasive crayfish pose, much of the research to date has been focused on lentic ecosystems, whilst the impact on stream communities has been poorly quantified in many regions (Stenroth and Nyström, 2003;Pysek et al, 2008;Lodge et al, 2012).…”
Section: Introductionmentioning
confidence: 99%